Swipe, Stream, and Splurge: Systematic Literature Review on The Triggers of Impulsive Buying in Live Streaming Commerce - Izzati, Astika Ulfah; Anindea, Frianka; Angguna, Welan Mauli; Andriansyah, Andriansyah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Recently live streaming has become popular media that enabling public to broadcast their video content through numerous platform (i.e., social media and e-commerce). In live streaming, live streamer could have real-time and interactive communication to their audience. Hence many people including marketer use live streaming as essential marketing tools that can shorten customer’s purchase decision time, and provoke customer’s impulse buying urge. Given the popularity of live steaming in numerous platform and impulse buying behavior become imperative topic in consumer behavior study, synthetizing the existing literature related to impulse buying in live streaming is needed. This study occupies the past and present of impulse buying in live streaming to gain better understanding of impulse buying in live streaming, and also gives insight about prospective of impulse buying in live streaming study for the future research. The author used secondary data from Scopus database in doing systematic literature review. In term of data extracting process, Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) is used, and 30 papers that meet the criteria are included to be reviewed. Author synthesize articles reviewed and found some findings such as studies progression, research design and methodology adopted in the reviewed article, theories used, and research theme. The research contributes to enhance theoretical and practical implications that is needed by academician for future research directions, and practitioners to strengthen their marketing strategy using live streaming feature to trigger people buy their product impulsively.